Scene-based spectral calibration assessment of high spectral resolution imaging spectrometers. - Guanter, L; Segl, K; Sang, B; Alonso, L; Kaufmann, H; Moreno, J (Optical Society of American (OSA), 2009)
An accurate knowledge of the spectral calibration of imaging spectrometers is required for optimum data processing and interpretation. The scene-based spectral characterization of imaging spectrometers is frequently necessary to update or replace the pre-flight laboratory-based spectral characterization supplied by the data provider. An automatic method for the estimation of spectral calibration parameters (channel position and bandwidth) at atmospheric absorption regions from high spectral resolution imaging spectrometers (spectral sampling interval below 5 nm) is presented in this contribution. The method has been tested on two commercial instruments with spectral sampling intervals below 2.5 nm. Optical aberrations such as smile, spectrometer shift and rotation and degradation of channel bandwidth have been detected and are discussed in terms of potential error sources at the instrument level.